Investigating the Role of Mo and Cr during the Activation and Passivation of Ni-Based Alloys in Acidic Chloride Solution. Issue 2 (18th February 2021) - Henderson, Jeffrey D.; Li, Xuejie; Filice, Fraser P.; Zagidulin, Dmitrij; Biesinger, Mark C.; Kobe, Brad; Shoesmith, David W.; Ogle, Kevin; Noël, James J.
Abstract : The elemental dissolution behaviour of commercially available Ni-based alloys was investigated in the context of surface activation, spontaneous passivation, and electrochemically-assisted passivation in hydrochloric acid solution using atomic emission spectroelectrochemistry (AESEC). Following surface activation, the spontaneous passivation of each alloy was found to proceed by the accumulation of mainly Mo-rich, but also Cr-rich oxides. An alloy's ability to recover from surface activation was found to improve with increased Mo content. For the alloy with the lowest Mo content considered here, approximately 8 wt.% Mo, spontaneous passivation was unsuccessful and active dissolution was observed. For alloys with higher Mo contents, greater than 13 wt.% Mo, spontaneous passivation occurred quickly, and dissolution rates stabilized at values comparable to those found for the native oxide, i.e., before perturbation by an applied potential. Mo(IV) oxides were found to be the species accumulating during spontaneous passivation using ex situ X-ray photoelectron spectroscopy (XPS). During electrochemically-assisted passivation, i.e., applying a potential within the passive region, a portion of the previously accumulated Mo was removed while Cr oxides accumulated at the surface. However, based on the dissolution rates observed after electrochemically-assisted passivation, Cr-content did not dictate the barrier layer properties.